2003
DOI: 10.1103/physrevd.68.024005
|View full text |Cite
|
Sign up to set email alerts
|

Radiation from accelerated black holes in a de Sitter universe

Abstract: Radiative properties of gravitational and electromagnetic fields generated by uniformly accelerated charged black holes in asymptotically de Sitter spacetime are studied by analyzing the C-metric exact solution of the Einstein-Maxwell equations with a positive cosmological constant Λ. Its global structure and physical properties are thoroughly discussed. We explicitly find and describe the specific pattern of radiation which exhibits the dependence of the fields on a null direction along which the (spacelike) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 37 publications
7
70
0
Order By: Relevance
“…The gravitational field near spacelike I thus takes the form 19) with two planes of symmetry, see figure 4(D). This directional dependence agrees with that for the C-metric spacetime with Λ > 0 derived recently in [102]. For Petrov type II spacetimes, only two PNDs coincide so that R 1 = tan θ1 2 , R 2 = tan θ2 2 exp(−iφ 2 ), R 3 = R 4 = 0.…”
Section: Radiation On Spacelike Isupporting
confidence: 76%
See 4 more Smart Citations
“…The gravitational field near spacelike I thus takes the form 19) with two planes of symmetry, see figure 4(D). This directional dependence agrees with that for the C-metric spacetime with Λ > 0 derived recently in [102]. For Petrov type II spacetimes, only two PNDs coincide so that R 1 = tan θ1 2 , R 2 = tan θ2 2 exp(−iφ 2 ), R 3 = R 4 = 0.…”
Section: Radiation On Spacelike Isupporting
confidence: 76%
“…For Λ > 0 it represents a pair of uniformly accelerated possibly charged black holes in de Sitterlike universe. In [102] we demonstrated that the corresponding electromagnetic field exhibits exactly the same asymptotic radiative behaviour at the spacelike conformal infinity I as for the test fields [101] of accelerated charges. Moreover, we found and explicitly described the specific analogous directional structure of the gravitational radiation field, and we proved that the directional pattern of radiation is adapted to the principal null directions of this Petrov type D spacetime.…”
Section: On Studies Of Asymptotic Behaviour Of Radiative Fields In Gementioning
confidence: 89%
See 3 more Smart Citations